2004
DOI: 10.1007/s10822-004-7878-1
|View full text |Cite
|
Sign up to set email alerts
|

Human topoisomerase I poisoning: docking protoberberines into a structure-based binding site model

Abstract: Using the X-ray crystal structure of the human topoisomerase I (top1) - DNA cleavable complex and the Sybyl software package, we have developed a general model for the ternary cleavable complex formed with four protoberberine alkaloids differing in the substitution on the terminal phenyl rings and covering a broad range of the top1-poisoning activities. This model has the drug intercalated with its planar chromophore between the -1 and +1 base pairs flanking the cleavage site, with the nonplanar portion pointi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…In one study, the X-ray crystal structures of the human topoisomerase I-DNA cleavable complex, combined with a Sybyl software package, have been used to analyse the properties of berberine as a potent topoisomerase I poison for a next generation anticancer drug (Kettmann et al, 2004a). Another study using NCI database by COMPARE analysis, investigated the responses of 60 cancer cell lines to berberine (the IC 50 values) and examined the correlation to another 43,177 compounds included in the database, in order to establish the molecular determinants of response of tumour cells to berberine.…”
Section: Computer-aided Molecular Design and Prediction Of Cell Respomentioning
confidence: 99%
“…In one study, the X-ray crystal structures of the human topoisomerase I-DNA cleavable complex, combined with a Sybyl software package, have been used to analyse the properties of berberine as a potent topoisomerase I poison for a next generation anticancer drug (Kettmann et al, 2004a). Another study using NCI database by COMPARE analysis, investigated the responses of 60 cancer cell lines to berberine (the IC 50 values) and examined the correlation to another 43,177 compounds included in the database, in order to establish the molecular determinants of response of tumour cells to berberine.…”
Section: Computer-aided Molecular Design and Prediction Of Cell Respomentioning
confidence: 99%
“…The minimum energy docked poses (Fig. S8) revealed that the complexes fit into the curve contour of the targeted DNA in the minor groove and are situated within the G-C (~13.2 Å) region, and they slightly bend the DNA in such a way that a part of the planar heterocyclic rings make favorable stacking interactions between DNA base pairs, leading to van der Waals interactions and hydrophobic contacts with the DNA functional groups that define the groove [65,66].…”
Section: Molecular Docking With Dnamentioning
confidence: 99%
“…Therefore, we studied the DNAbinding mode of these complexes to understand the preferred orientation and the type of interaction between the complexes and DNA. The energetically most favorable conformation of the docked pose (figures 4 and S2-S3) revealed that all complexes fitted into the minor groove region of DNA within G-C regions compared to A-T ones, and lead to van der Waals interactions and hydrophobic contacts with DNA functional groups which define the stability of the groove [51]. It is well known that, in contrast to major groove, small molecules preferentially interact with the minor groove due to little steric interference [52].…”
Section: Dna Molecular Docking Analysis Molecular Docking Simulationmentioning
confidence: 99%